2007
DOI: 10.1158/1055-9965.epi-07-0655
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer Risk and Erythrocyte Composition of Docosahexaenoic Acid with Anti-inflammatory Effects

Abstract: Infection with Helicobacter pylori is linked to inflammation and is the main cause of peptic ulcer, gastritis, and gastric malignancies. To examine associations between gastric cancer risk and the erythrocyte composition of docosahexaenoic acid (DHA), a fatty acid with antiinflammatory and apoptosis-inducing effects, here we conducted a case-control study of 179 incident gastric cancer cases and 357 noncancer controls (matched by age, sex, and season of sample collection). Dietary information and blood samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…However, in a cross-sectional study within the EPIC cohort, the weak correlations calculated at the individual level between plasma phospholipid oleic acid and olive oil or meat intake suggested that dietary contributors of plasma oleic acid concentrations may not be strong determinants compared with endogenous hepatic synthesis, mainly in countries with low olive intake (16). Thus, an increased risk of GC associated with a high level of oleic acid along with a high ratio of MUFAs to SFAs, as previously reported in GC (26) and breast cancer (24,27,28), might be mostly related to increased desaturation of stearic acid into oleic acid rather than to a diet rich in MUFAs. Diet may also have an important effect on SCD-1 activity.…”
Section: Discussionmentioning
confidence: 58%
“…However, in a cross-sectional study within the EPIC cohort, the weak correlations calculated at the individual level between plasma phospholipid oleic acid and olive oil or meat intake suggested that dietary contributors of plasma oleic acid concentrations may not be strong determinants compared with endogenous hepatic synthesis, mainly in countries with low olive intake (16). Thus, an increased risk of GC associated with a high level of oleic acid along with a high ratio of MUFAs to SFAs, as previously reported in GC (26) and breast cancer (24,27,28), might be mostly related to increased desaturation of stearic acid into oleic acid rather than to a diet rich in MUFAs. Diet may also have an important effect on SCD-1 activity.…”
Section: Discussionmentioning
confidence: 58%
“…Hence, the level of fish consumption, or any other DHA-rich food for that matter, does not constitute an adequate measure of DHA gastric concentration and DHA availability to H. pylori . This point is well illustrated by the fact that although no association between fish intake and gastric cancer risk could be drawn from the Japanese population, the percentage of DHA in the membrane composition of erythrocytes was directly associated with a lower risk of developing gastric cancer [33]. These arguments may justify the lack of a positive association between H. pylori gastric colonization/gastritis and high levels of PUFA supplementation in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…However data are as yet insufficient to draw firm conclusions. (37) , Japan 2011 (43) , China For gastric cancer, a Japanese case-control study (55) Relationship to the incidence of lung cancer was not recently investigated. A rather old prospective cohort study (56) in Norway (153 cases/25,956 men and 25,496 women aged 16 -56 years) showed an inverse association with intake of cod liver oil supplement (RR: 0‱5, CI: 0‱3-1‱0).…”
Section: Other Cancersmentioning
confidence: 99%